GE_GERICHTE P/6071/2016 vom 26. Januar 2018 - GE Cour de justice (2018)
VIOLATION D'UNE OBLIGATION D'ENTRETIEN ; INDEMNITÉ(EN GÉNÉRAL) | CP.217.al1; CP.47; CP.34; CPP.391.al2; CPP.433.al1; CPP.433.al2